Medical Students in Canadian Universities: Report of Statistics, 1963-64 and 1964-65 - Macleod, J. W. (1965)
Recognizing Canada's urgent need of physicians Canadian medical faculties have continued to increase first-year enrolment for the sixth successive year. Returns from the 12 medical schools showed that 1133 students began medical studies in 1964 compared with 1086 the previous year. Firstyear female students showed a decrease for the first time since 1959: 124 compared with 146 in 1963. Every tenth graduate is a woman; six years ago this ratio was one in 20. Loss of students from withdrawals and dismissals in 1963-64 occurred chiefly in the first year (9.2% as compared with 8.7% in 1962-63). Almost half of the loss in all four years of the course was for non-academic reasons. A decrease in American and a slight increase in Commonwealth and foreign first-year students was noted. Total foreign student enrolment continued to decline from a high of 485 in 1959-60 (13.7%) to 400 in 1964-65 (10.3%).